A transcriptional corepressor of Stat1 with an essential LXXLL signature motif - Liu, Bin (The National Academy of Sciences, 2001)
Interferon (IFN) treatment induces tyrosine phosphorylation and nuclear translocation of Stat1 (signal transducer and activator of transcription) to activate or repress transcription. We report here that a member of the protein inhibitor of activated STAT family, PIASy, is a transcriptional corepressor of Stat1. IFN treatment triggers the in vivo interaction of Stat1 with PIASy, which represses Stat1-mediated gene activation without blocking the DNA binding activity of Stat1. An LXXLL coregulator signature motif located near the NH(2) terminus of PIASy, although not involved in the PIASy–Stat1 interaction, is required for the transrepression activity of PIASy. Our studies identify PIASy as a transcriptional corepressor of Stat1 and suggest that different PIAS proteins may repress STAT-mediated gene activation through distinct mechanisms.